2011
DOI: 10.1111/j.1748-7692.2011.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Using aerial photography to investigate evidence of feeding by bowhead whales

Abstract: Aerial photographs were analyzed to investigate the feeding habits of the Bering‐Chukchi‐Beaufort (BCB) population of bowhead whales (Balaena mysticetus), particularly epibenthic feeding near Barrow, Alaska. Evidence of epibenthic feeding was based on mud visible on the dorsal surface of whales, resulting from feeding near the seafloor. Other cues used to assess feeding were an open mouth or the presence of feces in photographs. Over 3,600 photographs were analyzed including photos from surveys in spring and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It is also unclear how diet may support mineral deposition in baleen plates. Young whales may lack an adequate cross‐sectional area for a fully functioning feeding apparatus required for efficient surface‐ or water‐column feeding, and at least one yearling showed evidence it fed on benthic invertebrates such as euphausiids (Hazard & Lowry, 1984; Mocklin, Rugh, Moore, & Angliss, 2012; Werth & Sformo, in press). Unfortunately, we know nothing yet of the ontogenetic shifts in bone mineral density in other baleen whales, and future studies may address this gap.…”
Section: Discussionmentioning
confidence: 99%
“…It is also unclear how diet may support mineral deposition in baleen plates. Young whales may lack an adequate cross‐sectional area for a fully functioning feeding apparatus required for efficient surface‐ or water‐column feeding, and at least one yearling showed evidence it fed on benthic invertebrates such as euphausiids (Hazard & Lowry, 1984; Mocklin, Rugh, Moore, & Angliss, 2012; Werth & Sformo, in press). Unfortunately, we know nothing yet of the ontogenetic shifts in bone mineral density in other baleen whales, and future studies may address this gap.…”
Section: Discussionmentioning
confidence: 99%
“…Bowhead whales are occasionally known to feed in the western subregion during spring (Carroll et al, 1987;Lowry et al, 2004;Mocklin et al, 2012). Lowry et al (2004) found that 34% (31 of 91) of whales sampled during the spring harvest at Utqiaġvik showed some evidence of feeding, and Mocklin et al (2012) reported that 55% of aerial photos of whales near Point Barrow in May showed evidence of feeding near the seafloor (i.e., mud on their heads). However, the quantity of food in the stomach of whales sampled in spring tends to be much less than in autumn (Lowry et al, 2004) when their forestomachs are often full to capacity (North Slope Borough, unpubl.…”
Section: Spring Behaviormentioning
confidence: 99%
“…Studies to determine the importance of the Alaskan Beaufort Sea as a feeding ground for bowhead whales have produced somewhat conflicting results. Feeding behavior has been regularly observed during aerial surveys in autumn (Würsig et al, 2002; and occasionally in spring (Carroll et al, 1987;Mocklin et al, 2012). Analyses of stomach contents of harvested whales suggest that bowhead whales regularly find food in the Alaskan Beaufort Sea (Lowry and Burns, 1980;Lowry, 1993;Lowry et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aerial survey methods have been used successfully off Point Barrow, Alaska, to collect photo-identification data to estimate the abundance of the Western Arctic bowhead whale stock (Schweder 2003;Koski et al 2010;Schweder et al 2010;Mocklin et al 2012a;Vate Brattström et al 2016). Numerous studies of bowhead whale feeding behavior in the Alaska Arctic, specifically in the Barrow Canyon area (Mocklin et al 2012b) and in the eastern Alaska Beaufort Sea (Richardson and Thomson 2002), have been conducted from aircraft. Furthermore, aerial surveys have been used regularly to mitigate and monitor the effects of anthropogenic activities, such as petroleum exploration operations (e.g., Richardson et al 1985Richardson et al , 1986Richardson et al , 1987Schick and Urban 2000).…”
Section: Introductionmentioning
confidence: 99%